Branding “Tara La No Ate” pada Indonesia Creative Cities Festival (ICCF) - Lisda Ariani Simabur (JURNAL LENSA MUTIARA KOMUNIKASI, 2022)
The first aspect of the promotion of communication strategies can be concluded as "Tara La No Ate” branding at the 2019 Indonesia Creative Cities Festival (ICCF) aiming to revive, promote, and introduce Ternate as a Creative Economy City, and also as tangible evidence of the implementation of the communication promotion strategy and branding “Tara La No Ate which becomes the theme and raises local wisdom from the city of Ternate so that the use of the media can be the manifestation of the communication promotion strategy process. The second aspect of the branding elements at the 2019 ICCF in Ternate is to convey a positive image contained in the message in the series of events which becomes part of the local wisdom and history that exists in Ternate and is shown to stakeholders and the wider community to be known directly through the 2019 ICCF performance. The branding elements include brand name, logo, visual appearance, spokesperson, voice, and remarks related to ICCF 2019 in Ternate